Nilai Fisiologis Sapi Perah Kering Kandang di Pangalengan: Hematologi, Denyut Jantung, Frekuensi Respirasi, dan Suhu Tubuh - Agik Suprayogi; Khairul Ihsan; Asep Yayan Ruhyana (Jurnal Ilmu Pertanian Indonesia, 2019)
Pangalengan is at an altitude of 1000-1400 m above sea level with annual temperatures range of 12-28°C and annual humidity of 60-70%. Pangalengan's environmental conditions can affect the physiological conditions and health of dairy cattle, especially during the dry period. The information about the physiological value of dairy cows when they are in a dry period is not yet available. This study used 46 dairy cows that were on a dry period, and measurements of physiological parameters were carried out in the morning, afternoon, and evening. Heart rate, respiration rate, and body temperature ranges were 52,8-70,2 times/min, 18.9−36.6 times/min, and 37,6-38,6°C, respectively. The ranges of hemoglobin, hematocrit, erythrocytes, and leukocytes were 9.3-11.3 g/dl; 30.4-36.6%; 6.5-8.70 million/µl; and 7.4-12.8 thousand/µl, respectively. The differential ranges of leukocytes including lymphocytes, neutrophils, monocytes, eosinophil, and basophils were at 29.60-55.60%; 28.80-56.20%; 0.30-4.30%; 5.50-19.7%; and 0.00-0.00%, respectively. The neutrophil/lymphocyte ratio was obtained in the range of 0.45-1.91. This study concluded that dairy cows during dry period maintained in mild Pangalengan climatic conditions showed physiological values that were within the normal range.